Corporate Social Responsibility Program Implementation through Art Event - Geral Al Hadaq; Mufid Salim; Adela Gita N; Lana Qurratul A; Anugerah Bella T; Nadila Wahyuni (Palakka : Media and Islamic Communication, 2020)
The Corporate Social Responsibility program is a program created by a company for people who live around the company or communities that are affected by the existence of the company, the CSR program was created to provide a positive image for the company. Besides, the CSR program is also designed to improve the welfare of the community and the surrounding environment as well as a sense of the company's responsibility towards the various parties involved and those affected either directly or indirectly. So that the CSR program, can improve the company's positive image. The community and stakeholders will give a positive view of the company if the company can be accountable properly to the stakeholders. This study aims to observe the CSR program contained in the Pandanaran Prawirotaman Hotel Yogyakarta, namely to find out how a CSR program is implemented and what benefits the company gets, as well as to find out how reciprocity is from the community to the CSR program carried out by Pandanaran Hotel Prawirotaman Yogyakarta. Data collection using observational techniques, literature study, and interviews are carried out in this study. The results of this study indicates that the CSR program created at Hotel Pandanaran is very much adapted to the location of the hotel in the area where many foreign tourists come. The Pandanaran Hotel Public Relations Team also considers that the CSR program in the form of art activities is one of the gaps and opportunities for the existence of the hotel itself.